2003
DOI: 10.1007/s00125-003-1081-0
|View full text |Cite
|
Sign up to set email alerts
|

Prior short-term consumption of resistant starch enhances postprandial insulin sensitivity in healthy subjects

Abstract: Aims/hypothesis. Diets rich in insoluble-fibre are linked to a reduced risk of both diabetes and cardiovascular disease; however, the mechanism of action remains unclear. The aim of this study was to assess whether acute changes in the insoluble-fibre (resistant starch) content of the diet would have effects on postprandial carbohydrate and lipid handling. Methods. Ten healthy subjects consumed two identical, low-residue diets on separate occasions for 24 h (33% fat; <2 g dietary fibre). Of the diets one was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
178
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(189 citation statements)
references
References 45 publications
7
178
2
2
Order By: Relevance
“…However, both highly fermentable insoluble resistant starch [7,27] and only moderately fermentable insoluble cereal fiber [8,14] increased insulin sensitivity in humans, indicating that a dose-dependent relation between fermentability of dietary fibers and insulin sensitivity is unlikely [3]. Further, available studies indicate that SCFA could contribute to increased de novo lipogenesis [24], probably by stimulating adipogenesis through Gpr43 [18], although in the present study Gpr43 expression was not significantly increased in fermentable fiber fed mice.…”
Section: Discussioncontrasting
confidence: 73%
“…However, both highly fermentable insoluble resistant starch [7,27] and only moderately fermentable insoluble cereal fiber [8,14] increased insulin sensitivity in humans, indicating that a dose-dependent relation between fermentability of dietary fibers and insulin sensitivity is unlikely [3]. Further, available studies indicate that SCFA could contribute to increased de novo lipogenesis [24], probably by stimulating adipogenesis through Gpr43 [18], although in the present study Gpr43 expression was not significantly increased in fermentable fiber fed mice.…”
Section: Discussioncontrasting
confidence: 73%
“…Enhanced carbohydrate handling on the second day after consumption of RS has recently been shown [45]. The authors attributed the observed effects to increased colonic fermentation with higher short-chain fatty acid concentrations in the portal vein, and thereby improved glucose metabolism, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The consumption of 60 g of RS from HAM-RS2 in 10 healthy participants resulted in significantly lower postprandial glycemia and insulin levels with improved insulin sensitivity on the following day. 34 Robertson et al 35 also found significant improvements in insulin sensitivity but not glycemia in 10 healthy individuals who consumed 30 g/day of RS from HAM-RS2 for 4 weeks. Another study 36 found that, although postprandial glucose concentrations in 20 healthy participants who consumed 48 g of RS from HAM-RS2 did not differ from those of control subjects, the individuals consuming the HAM-RS2 had lower energy intakes at dinner after the two test meals and throughout 24 hours.…”
Section: Rs Effectsmentioning
confidence: 93%